Factors Influencing Adoption of Sericultural Technologies - S. Lakshmanan (Journal of Agricultural Extension Management, 2025)
This study examines factors influencing adoption of sericultural technologies by farmer households in MaiavalIi taluk of Mandya district in Karnataka. The results reveal that adoption of HYV of mulberry and rearing of CSR hybrids were significantly influenced by cocoon price, extension support and family labour. To increase adoption level in the study villages in particular and in general in Karnataka, the Department of Sericulture (DOS) has to encourage new farmers through free supply of HYV mulberry cuttings and arrange credit to construct rearing house and organize training for the farmers to rear CSR silkworm races. In addition, DOS has to maintain stable cocoon price to assure that sericulture is more profitable and sustainable.